Penyelesaian Kredit Tak Tertagih Berlandaskan Pada Asas Sepenanggungan - Widharmayanti, Ni Nyoman Alit; Dewi, Putu Eka Dianita Marvilianti (Universitas Pendidikan Ganesha, 2021)
This study aims to see (1) the process of applying for credit to AMER's Banjar suka duka, (2) the causes of uncollectible credit by AMER joy and sorrow members, (3) how to solve the problem of uncollected credit by AMER's joy and sorrow members. Methods of interview data, observation and documentation carried out in Banjar Suka Duka AMER. Processing the collected data then analyzed through data reduction, data presentation and drawing conclusions. The results showed that (1) the lending of credit by members of the AMER's joy and sorrow may use the names of other members based on mutual trust and solidarity between members. So that the borrowing of members' names in credit applications is commonplace and is accepted by AMER's Banjar Management. 2) The cause of uncollectible credit in the AMER joy and sorrow banjar is a very easy redit lending system without the use of collateral and regulations that bind members to repay their credit. (3) The problem of uncollectible credit in the banjar of AMERica, which did not find a solution for two years, was finally implemented as a cover. Where in applying as penenanggunga in the member credit interest is whitened and the principal of the member is able to pay.Â